Analysis of The Influence of Liquidity, Credit and Operational Risk, in Indonesian Islamic Bankâs Financing for The Period 2007-2013 - Diallo, Ousmane; Fitrijanti, Tettet; Tanzil, Nanny Nanny (Gadjah Mada International Journal of Business, 2015)
The purpose of this paper is to analyze the influence of credit, liquidity and operational risks in six Indonesianâs islamic banking financing products namely mudharabah, musyarakah, murabahah, istishna, ijarah and qardh, in order to try to discover whether or not Indonesian islamic banking is based on the ârisk-sharingâ system. This paper relies on a fixed effect model test based on the panel data analysis method, focusing on the period from 2007 to 2013. The research is an exploratory and descriptive study of all the Indonesian islamic banks that were operating in 2013. The results of this study show that the Islamic banking system in Indonesia truly has banking products based on ârisk-sharing.â We found out that credit, operational and liquidity risks as a whole, have significant influence on mudarabah, musyarakah, murabahah, istishna, ijarah and qardh based financing. There is a correlation between the credit risk and mudarabah based financing, and no causal relationship between the credit risk and musharaka, murabahah, ijarah, istishna and qardh based financing. There is also correlation between the operational risk and mudarabah and murabahah based financing, and no causal relationship between the operational risk and musharaka, istishna, ijarah and qardh based financing. There is correlation between the liquidity risk and istishna based financing, and no causal relationship between the liquidity risk and musharaka, mudarabah, murabahah, ijarah and qardh based financing. A major implication of this study is the fact that there is no causal relationship between the credit risk and musharakah based financing, which is the mode of financing where the islamic bank shares the risk with its clients, but there is an influence of credit risk toward mudarabah mode financing, a financing mode where the Islamic bank bears all the risk. These findings can lead us to conclude that the Indonesian Islamic banking sector is based on the ârisk sharingâ system.